Effectiveness of 190 μg Fluocinolone Acetonide and 700 μg Dexamethasone Intravitreal Implants in Diabetic Macular Edema Using the Area-Under-the-Curve Method: The CONSTANT Analysis - Zarranz-Ventura J (Dove Medical Press, 2020)
Javier Zarranz-Ventura, 1, 2 Joshua O Mali 3 1Clinical Institute of Ophthalmology (ICOF), Hospital Clinic, Barcelona, Spain; 2August Pi i Sunyer Biomedical Research Institute (IDIBAPS), Barcelona, Spain; 3The Eye Associates, Sarasota, FL, USACorrespondence: Javier Zarranz-VenturaClinical Institute of Ophthalmology (ICOF), Hospital Clinic, Barcelona, SpainTel +34 932 275 400Email jzarranz@hotmail.comPurpose: Calculations of area-under-the-curve (AUC) provide the average letters gained across the entire treatment period, which may be a better estimate of long-term effectiveness than single time-point outcomes, particularly when it comes to sustained-release therapies.Materials and Methods: The AUC method was used to compare the efficacy of the 0.2 μg/day fluocinolone acetonide (total dose of 0.19 mg; FAc) and dexamethasone (DEX) 700 μg implants based on published data from their respective Phase 3 FAME (Fluocinolone Acetonide for Macular Edema) and MEAD pivotal clinical trials in diabetic macular edema (DME). Best-corrected visual acuity (BCVA) letter scores were collated from the FAME trial and compared with those reported in MEAD. The trapezoidal rule was then used to calculate AUC, based on BCVA letter score, from baseline to Month 36 (FAME)/Month 39 (MEAD) and presented as an overall mean visual acuity change per day.Results: Treatment with either the FAc or DEX implant resulted in an improved BCVA over the treatment period compared with sham. This effect was statistically greater (p=0.029) for the FAc implant than the DEX implant (5.2 vs 3.5 letters/day, respectively) and even greater in the recurrent DME subgroup (p< 0.001; 6.9 vs 3.5 letters/day, respectively).Conclusion: Although direct comparisons between trial cohorts cannot be performed, this analysis indicated that, in their respective pivotal clinical trial cohorts, treatment with the FAc implant provides better long-term visual acuity outcomes and a lower treatment burden than achieved with the DEX implant.Keywords: area-under-the-curve, best-corrected visual acuity, diabetic macular edema, corticosteroid, fluocinolone acetonide implant, dexamethasone implant